PENGARUH STRATEGI TINGKAT BISNIS, PERSAINGAN PASAR, DAN LEVERAGE TERHADAP MANAJEMEN LABA - Winny Brigita; Agustinus Santosa Adiwibowo (Diponegoro Journal of Accounting, 2017)
The purpose of this study is to explore the impact among business strategy, market competition, leverage and earnings management. This study uses Porter’s typology of business strategies; cost leadership and differentiation. First, it examines the relationships between business strategy and earnings management. Further, it analyzes the joint effect of business strategy and market competition to earnings management. Furthermore, the researcher examined the relationship between leverage to earnings management.This study uses secondary data. The population consists of manufacturing  firms listed in Indonesia Stock Exchange. This study uses purposive sampling and takes some criterias. Firms included in this study are being listed in IDX before 2011 and also provides annual reports from 2012 until 2014. The samples consists of 129 observations. In this research Ordinary Least Square used to be analysis technique.The result of this study show that firms that follow cost leadership strategy (cost leaders) are more likely to have a higher level of real earnings management and  firms that follow differentiation strategy (differentiators) are less likely to use real earnings management. For cost leaders, the market competition further increases the level of real earnings management, whereas the level of earnings management of differentiators is also significantly impacted by the market competition. Furthermore, the results show that leverage within the company has no significant effect on earnings management